2018
DOI: 10.7160/aol.2018.100403
|View full text |Cite
|
Sign up to set email alerts
|

Food-Biofuels Interactions: The Case of the U.S. Biofuels Market

Abstract: Corn refers to the main feedstock for U.S. biofuels production and together with soybean oil, as typical biofuel food commodity that can be converted into biodiesel, accounts for over 90 percent of biofuels production in the United States. The paper focuses on the nexus of agri-food and energy markets in U.S. and investigates the interrelationships between the biofuel prices and prices of soybean oil, corn and wheat. Co-integration analysis and vector error correction model are carried out in order to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Such an understanding of energy security is also referred to in various academic publications and research projects (Sovacool et al, 2011, Cherp & Jewell, 2011. Thus, it can be observed that a number of research projects emphasise an interdisciplinary approach to energy security (Månsson, 2014;Cipollaro & Lomonaco, 2016;Löschel, Moslener, & Rübbelke, 2010;Kapustová, Kapusta, & Bielik, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such an understanding of energy security is also referred to in various academic publications and research projects (Sovacool et al, 2011, Cherp & Jewell, 2011. Thus, it can be observed that a number of research projects emphasise an interdisciplinary approach to energy security (Månsson, 2014;Cipollaro & Lomonaco, 2016;Löschel, Moslener, & Rübbelke, 2010;Kapustová, Kapusta, & Bielik, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For China, Deng et al [76] calculated the cost efficiency of Jatropha curcas biodiesel with positive results albeit with a smaller discount rate. Use of biofuels was also discussed for Germany and the United States [77][78][79]. The results show that net present value is mostly positive for discount rates ranging from 1 to 11%.…”
Section: Resultsmentioning
confidence: 99%